2013
DOI: 10.1073/pnas.1316622110
|View full text |Cite
|
Sign up to set email alerts
|

Conversion from CUL4-based COP1–SPA E3 apparatus to UVR8–COP1–SPA complexes underlies a distinct biochemical function of COP1 under UV-B

Abstract: The evolutionarily conserved CONSTITUTIVE PHOTOMORPHOGENESIS 1 (COP1) is a RING and WD40 protein that functions as a substrate receptor of CULLIN4-DAMAGED DNA BINDING PROTEIN 1 (CUL4-DDB1)-based E3 ubiquitin ligases in both plants and animals. In Arabidopsis, COP1 is a central repressor of photomorphogenesis in the form of COP1-SUPPRESSOR OF PHYA (SPA) complex(es). CUL4-DDB1-COP1-SPA suppresses the photomorphogenic program by targeting the transcription factor ELONGATED HYPOCOTYL 5 for degradation. Intriguingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
200
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 171 publications
(205 citation statements)
references
References 27 publications
4
200
0
1
Order By: Relevance
“…These dilemmas are not specific to the results for HY5 but represent general uncertainties when interpreting ChIP data. In addition, it is yet uncertain whether the UV-Binduced HY5 association with chromatin of target genes primarily reflects the stabilization of the HY5 protein (Favory et al, 2009;Huang et al, 2013) or the activity of the HY5 protein is affected otherwise by UV-B. It was previously reported that phosphorylation of HY5 within its COP1 binding domain may regulate HY5 stability and activity .…”
Section: Regulation Of the Hy5 Association With Chromatinmentioning
confidence: 99%
See 1 more Smart Citation
“…These dilemmas are not specific to the results for HY5 but represent general uncertainties when interpreting ChIP data. In addition, it is yet uncertain whether the UV-Binduced HY5 association with chromatin of target genes primarily reflects the stabilization of the HY5 protein (Favory et al, 2009;Huang et al, 2013) or the activity of the HY5 protein is affected otherwise by UV-B. It was previously reported that phosphorylation of HY5 within its COP1 binding domain may regulate HY5 stability and activity .…”
Section: Regulation Of the Hy5 Association With Chromatinmentioning
confidence: 99%
“…HY5 itself, as well as HYH, is one of the UVR8-and COP1-regulated genes (Brown et al, 2005;Oravecz et al, 2006;Favory et al, 2009), but the transcription factor(s) and cis-regulatory element(s) mediating its transcription are not known. HY5 is also known to be posttranslationally stabilized by UV-B (Favory et al, 2009;Huang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Upon perception of UV-B light, UVR8 is activated by undergoing a dimer-to-monomer conformational change (5)(6)(7). The monomerization of UVR8 allows it to associate with the tetrameric constitutively photomorphogenic 1-suppressor of PHYA (COP1-SPA) core complex (8). This association, in turn, drives the release of COP1-SPA from the cullin 4-damaged DNA-binding protein 1 (CUL4-DDB1) E3 apparatus that represses light signaling under various light conditions (8,9).…”
mentioning
confidence: 99%
“…The monomerization of UVR8 allows it to associate with the tetrameric constitutively photomorphogenic 1-suppressor of PHYA (COP1-SPA) core complex (8). This association, in turn, drives the release of COP1-SPA from the cullin 4-damaged DNA-binding protein 1 (CUL4-DDB1) E3 apparatus that represses light signaling under various light conditions (8,9). The UV-B-dependent UVR8-COP1-SPA complex then acts as a molecular switch to turn on downstream signaling, including positively modulating the stability and activity of a central photomorphogenesis-promoting transcription factor, elongated hypocotyl 5 (HY5) (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation